SUPER BOWL ADS IN THE PERIOD FROM 2017-2022 - Alčaković, Slavko (The European Journal of Applied Economics, 2023)
Advertising during Super Bowl commercial breaks has become a crucial part of brands' marketing strategies, offering them the chance to reach a huge audience. Over the past six years, Super Bowl ads have been diverse and captivating, showcasing products from various categories such as food and beverage, cars, beer, financial and online services. The article provides a brief and overall analysis of Super Bowl ads from 2017 to 2022. The database used in the analysis was taken from the world-famous database at adsoftheword.com. This research analyzed the length, logo viewability and product category, presence of celebrities, animals, humor and average likability score
Keywords: advertising, super bowl, humor, celebrity, animals, likability of ads